air hangat PENGARUH PERENDAMAN KAKI DENGAN AIR HANGAT TERHADAP KUALITAS TIDUR REMAJA: PENGARUH PERENDAMAN KAKI DENGAN AIR HANGAT TERHADAP KUALITAS TIDUR REMAJA - Shihab, Ahmad Rizky Farras; Kusumawati, Yoni Rustiana; Rustanti, Marti (Journal of Local Therapy, 2024)
Background: adolescence is a transitional period where individuals experience physical changes and psychological development starting at the age of 12-20 years. These changes can cause problems that affect development, health and sleep quality. To improve sleep quality, foot bath in warm water Objective: to determine the effect of foot bath in warm water on the quality of sleep in adolescents. Research design: two group pre and post test. Research subject: there were 30 students from the Department of Physiotherapy, Health Polytechnic, Surakarta, who were divided into two groups, where group one was given intervention for 7 consecutive days and the research instrument used PSQI. Research result : the independent t-test showed that there was an influence on adolescent sleep quality. Conclusion : foot bath in warm water has an effect on improving the quality of sleep in adolescents.